Revisiting the history of fertility concentration and its measurement - Bilal Barakat (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2014)
To date, the concentration of fertility has been studied almost exclusively through the lens of indicators derived from the Lorenz curve of completed parity. Arguably, this situation has resulted from a misapplication of criteria from the study of income inequality, without fully considering the distinctive characteristics. Here, alternative measures of concentration are justified on substantive grounds and applied to a wide range of empirical data from developing, transitional, and industrialised countries. In particular, the traditional scale-invariant concentration measures are complemented by translation-invariant and intermediate perspectives. The latter conveniently also connects the nonparametric indicator approach to the study of fertility concentration with established statistical models for count data. This connection provides the missing link for the kind of behavioural interpretation of fertility concentration dynamics that has been attempted in the past, but can be shown to have been ill-founded.Examining the phenomenon of fertility concentration through this tri-focal lens leads to a picture that is more coherent, more parsimonious, and more complete.
Keywords: 300; Fertility; parity distribution; concentration; inequality